Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11547-007-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

3.0-T morphological and angiographic brain imaging: a 5-years experience

Abstract: Ever since the introduction of magnetic resonance (MR), imaging with 1.5 Tesla (T) has been considered the gold standard for the study of all areas of the body. Until not long ago, higher-field MR equipment was exclusively employed for research, not for clinical use. More recently, the introduction of 3.0-T MR machines for new and more sophisticated clinical applications has resulted in important benefits, especially in neuroradiology. Indeed, their high gradient power and field intensity (3.0 T) allow adjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(84 reference statements)
0
4
0
2
Order By: Relevance
“…turbo spin echo (TSE) and turbo field echo (TFE)], even though the increase in TR in all sequences -as will be explained below -partially compensates the Introduzione L'evoluzione delle apparecchiature utilizzate nell'imaging clinico ha conosciuto negli ultimi anni un'importante accelerazione. Per quanto riguarda la risonanza magnetica, l'attenzione si 猫 concentrata sulla realizzazione di tomografi ad elevato campo magnetico statico; apparecchi da 3 T sono presenti in diversi centri e sono ormai numerosi gli studi volti a comprendere i benefici e le problematiche da questi derivanti sui diversi apparati, con particolare attenzione rivolta al sistema nervoso centrale [1][2][3]. L'aumento del rapporto segnale-rumore, garantito dagli apparecchi di risonanza magnetica (RM) da 3 T, trova vaste applicazioni in ambito muscolo-scheletrico con interessanti potenzialit脿 per quanto concerne la valutazione di tendini, cartilagine, osso e legamenti.…”
Section: Technical Featuresunclassified
See 3 more Smart Citations
“…turbo spin echo (TSE) and turbo field echo (TFE)], even though the increase in TR in all sequences -as will be explained below -partially compensates the Introduzione L'evoluzione delle apparecchiature utilizzate nell'imaging clinico ha conosciuto negli ultimi anni un'importante accelerazione. Per quanto riguarda la risonanza magnetica, l'attenzione si 猫 concentrata sulla realizzazione di tomografi ad elevato campo magnetico statico; apparecchi da 3 T sono presenti in diversi centri e sono ormai numerosi gli studi volti a comprendere i benefici e le problematiche da questi derivanti sui diversi apparati, con particolare attenzione rivolta al sistema nervoso centrale [1][2][3]. L'aumento del rapporto segnale-rumore, garantito dagli apparecchi di risonanza magnetica (RM) da 3 T, trova vaste applicazioni in ambito muscolo-scheletrico con interessanti potenzialit脿 per quanto concerne la valutazione di tendini, cartilagine, osso e legamenti.…”
Section: Technical Featuresunclassified
“…The increase in SNR and spatial resolution of the 3 T system makes up for most shortcomings of 1.5 T imaging. Recent studies [5,26] demonstrated an increase in CNR at 3 T between articular fluid and cartilage, which could further facilitate evaluation of the latter [2]. Recently, many researchers have focussed on changes in T2 relaxation time of articular cartilage as an early indicator of osteoarthrosis (Fig.…”
Section: Ginocchiomentioning
confidence: 99%
See 2 more Smart Citations
“…7,12 Time-resolved imaging of contrast kinetics is a new technique for time-resolved 3D MR digital subtraction angiography 13 that can achieve temporal and spatial resolution high enough to evaluate AVMs, 4,8,9,16,31 especially Assessment of arteriovenous malformations with 3-Tesla time-resolved, contrast-enhanced, three-dimensional magnetic resonance angiography combined with a 3-T MR imaging unit. 2,3,22 In this study, we investigate the accuracy of 3-T TRICKS in the assessment of AVMs compared with conventional catheter angiography.…”
mentioning
confidence: 99%